2013
DOI: 10.1186/1472-6963-13-512
|View full text |Cite
|
Sign up to set email alerts
|

Parent experiences of inpatient pediatric care in relation to health care delivery and sociodemographic characteristics: results of a Norwegian national survey

Abstract: BackgroundThe national survey of parent experiences with inpatient pediatric care contribute to the Norwegian system of health care quality indicators. This article reports on the statistical association between parent experiences of inpatient pediatric care and aspects of health care delivery, child health status and health outcome as assessed by the parents, and the parents’ sociodemographic characteristics.Methods6,160 parents of children who were inpatients at one of Norway’s 20 pediatric departments in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Additionally, 60% reported that their economic needs were not taken care of. One Norwegian study have explored the satisfaction and experience of patients or relatives including a question regarding the hospital facilities [ 3 ].They reported a good satisfaction with the hospital facilities. The family members in the present study found the facilities for the patients to be generally satisfying but the facilities supporting rest and accommodation for family members to be poor has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 60% reported that their economic needs were not taken care of. One Norwegian study have explored the satisfaction and experience of patients or relatives including a question regarding the hospital facilities [ 3 ].They reported a good satisfaction with the hospital facilities. The family members in the present study found the facilities for the patients to be generally satisfying but the facilities supporting rest and accommodation for family members to be poor has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Severe traumatic brain injury (TBI) is internationally recognized as a major public health problem causing death and disability [ 1 – 3 ]. For survivors of severe TBI, the most common disabilities are associated with cognitive and behavioural deficits, which can impact the injured, caregivers and other family members for a long period of time [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Houve textos que estavam presentes em mais de uma temática. As temáticas e suas respectivas referências foram: (a) as limitações do cuidado biomédico: Pescosolido, 2006;Brown e Flores, 2011;Burkhart e Hogan, 2008;Bahar et al, 2005;Edwards, Staniszweska e Crichton, 2004;Smith, 2009;Zimmermann e Rodin, 2004; (b) a sociabilidade nas ações de cuidado: Pescosolido, 2006;Carpentier, 2013;Carpentier e Grenier, 2012;Farrant e Watson, 2004;Denier, 2008;Dovidio et al, 2008;Ferlander, 2007;Fine, 2005 ;Greenhalgh, Robb e Scambler, 2006;Noone e Stephens, 2008;Prior, 2003;Salvalaggio et al, 2013;Sorensen e Iedema, 2008;Spates, 2012;Andersen et al, 2011; (c) o entrelaçamento entre cuidado e subjetividade: Pescosolido, 2006; Brown e Flores, 2011; Edwards, Staniszweska e Crichton, 2004;Zimmermann e Rodin, 2004;Carpentier, 2013;Basu, 2006;Hudson et al, 2006 ;Levy, 2005;Lopez, 2006;Schouffoer et al, 2011;Solheim e Garratt, 2013;Turner et al, 2003;Weeber, 2005;Wajid, White e Karim, 2013; práticas integrativas e complementares: Daykin, McClean e Bunt, 2007;Freidin e Timmermans, 2008;Gyasi et al, 2011;Isola, 2013;…”
Section: Resultsunclassified
“…To ensure the content validity in the questionnaire developmental process, items from previous questionnaires assessing the experience of in-hospital patients [1214] and parents [22, 23] were consulted. Further, selection of items was based on interviews with family members and the expert knowledge of the authors (i.e., UMS, CA and AA) on rehabilitative care after severe TBI or other acquired brain injuries.…”
Section: Methodsmentioning
confidence: 99%
“…There are family satisfaction questionnaires for use in the intensive care units [2, 20, 21], and parents’ views have been increasingly used in the evaluation of care quality for children [22, 23]. Theoretically close relatives to surviving injured patients have comparable in-hospital experiences to parents with chronically ill children, so we searched for a suitable parent experience instrument covering multiple dimensions of care.…”
Section: Introductionmentioning
confidence: 99%